Prescription Pattern of Immunosuppressants Used in Post-Transplant Patients - Haldar, Biswajit; Varghese, Ashly Ann; Begum, Jesmina; Manna, Suman (Journal of Pharmacy Practice and Community Medicine)
Background: Organ transplantation is a life-saving medical operation in which a healthy graft from a donor is used to replace a failing or diseased organ. Maintaining graft survival and preventing allograft rejection require lifelong immunosuppressive treatment. Objectives: The purpose of this retrospective observational study was to examine the immunosuppressive medication prescription trend among post-transplant patients at a Bengaluru tertiary care facility. Materials and Methods: Over the course of 6 months, 107 prescriptions were examined. Results: The greatest-age group was 41-50 years old (32.7%), with men making up most patients (81.7%). Tacrolimus, prednisolone, and mycophenolate mofetil was the most often given combination (22.4%), followed by tacrolimus, mycophenolate sodium, and prednisolone, 18.7%. Tacrolimus alone was prescribed to 6 patients (5.6%) for maintenance therapy, whereas dual therapy was less prevalent, with tacrolimus and prednisolone, 6.5% being the most common combo. Conclusion: The study comes to the conclusion that triple immunosuppressive medication is still the recommended method for post-transplant care and that organ transplantation was more common in men. Because of its efficacy and safety, tacrolimus remains the mainstay medication in both single and combo regimens.
Keywords: Heart Transplantation; Immunosuppressant; Induction Therapy; Liver Transplantation; Lung Transplantation; Maintenance Therapy; Prescription Pattern; Rejection Therapy; Renal Transplantation.